On collecting : an investigation into collecting in the European tradition. - Pearce, Susan M. (London : Routledge, 2003)
- Collecting processes##- Themes and parameters##- Archaic themes of the long term##- Mediterranean themes##- Early modernist collectors##- Classic modernist collecting##- Collecting in a post-modernist world##- Collecting culture##- Collecting ourselves##- Controlling collecting##- Engendering collections##- Collecting relationships##- Collecting in time##- Collecting in space##- Material identities##- Political parameters##- The politics of value##- Collecting the other, within and without##- The other beyond and before##- Collecting the shape of things to come##- Relating collective values##- Vested interests##- Collecting in the European tradition.
CCS Gent
boek